Faktor-Faktor yang Mempengaruhi Mobilitas Penduduk (Studi Literatur pada Aspek Sosial, Ekonomi, dan Lingkungan) - Dudiyanto Pakaya (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2026)
Population mobility is a dynamic phenomenon that plays an important role in regional development processes. Population movement is influenced by various interconnected factors, particularly social, economic, and environmental aspects. This study aims to analyze the factors influencing population mobility using a Systematic Literature Review (SLR) approach. Data were collected from relevant national and international scientific literature published within the last ten years. The results indicate that economic factors are the primary determinants driving population mobility, particularly in relation to employment opportunities and income improvement. Meanwhile, social factors such as education and social networks act as supporting elements in the mobility process. Environmental factors also show significant influence, especially in the context of climate change, natural disasters, and environmental degradation. The interaction among these factors demonstrates that population mobility is a multidimensional phenomenon that requires a comprehensive analytical approach. This study is expected to contribute to the development of population studies and serve as a reference for sustainable development policy formulation.